David Smells! - David Shannon (Fareham, United Kingdom Blue Sky Press, 2005)
Caldecott Honor artist David Shannon is back with a third original board book that features the star of the bestselling No, David! books as a troublemaking toddler and introduces the five senses. Hey! What's that smell?! Join David as he discovers the five senses: touch, hear, see, smell, and taste. From petting the dog to banging on a drum, David knows how to have a good time. But he also knows that there's nothing better than playing a game with Mama at the end of a busy and exciting day. With the same irresistible humor and vibrant style as his award-winning No, David! books, David Shannon takes us back to the "early years" of his most beloved character. Perfect for beginning readers as well as for the youngest children!
Keywords: Board Book